Literature Review Of The Relationship Between Anemia In Pregnant Women And The Incidence Of Low Birth Weight - Zahroh, Fatimatul; Wulandari, Rr. Catur Leny (Jurnal Maternitas Kebidanan, 2025)
Anemia occurs when there are not enough red blood cells to meet the body's physiological needs. Anemia in pregnant women can affect the likelihood of low birth weight babies (LBW). This article aims to find out the relationship between anemia in pregnant women and the incidence of low birth weight. The search method was carried out through online databases, such as Goggle Scholars and Pubmed which were in accordance with the inclusion criteria in 5 national journals and 5 international journals. The results of ten analyzes from five national journals and five international journals from 2019 to 2024 show that there is a link between anemia in pregnant women and the incidence of low birth weight babies (LBW). However, one journal stated that there was no association between anemia in pregnant women and the incidence of low birth weight babies (LBW).